2020
DOI: 10.1177/1368430219892698
|View full text |Cite
|
Sign up to set email alerts
|

Group-level integrative complexity: Enhancing differentiation and integration in group decision-making

Abstract: Decision-making in organizations is often complex and involves groups, which have access to the pool of perspectives and knowledge their members hold individually. However, groups frequently fail to use their full decision-making potential. The concept of integrative complexity (IC) captures how complex decision-making profits from the differentiation and integration of diverse perspectives and knowledge. In a laboratory experiment with 4 conditions ( N = 12 groups of 4 students per condition), we found that g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 83 publications
0
15
0
Order By: Relevance
“…Research has repeatedly shown that lower in comparison with higher levels of integrative complexity are associated with increases in conflict escalation (Suedfeld & Leighton, 2002;Tetlock, 1985), aggressive acts (Satterfield, 1998), competitive strategies (Kugler & Brodbeck, 2014;Walker & Watson, 1994), tension and stress (Suedfeld, 1992;, violence (Suedfeld, Tetlock, & Ramirez, 1977), and international crises (Ballard, 1983;Suedfeld & Bluck, 1988;. In contrast, higher levels of integrative complexity have been shown to be related to more cooperative agreements, peaceful resolutions (Koo, Han, & Kim, 2002;Liht, Suedfeld, & Krawczyk, 2005;Winter, 2007) and constructive inter-and intra-group processes (Brodbeck, Kugler, Fischer, Heinze, & Fischer, 2020;Park & DeShon, 2018). Hypothesis 1.…”
Section: Research Parameters For Assessing Complexity In Potentially mentioning
confidence: 94%
See 2 more Smart Citations
“…Research has repeatedly shown that lower in comparison with higher levels of integrative complexity are associated with increases in conflict escalation (Suedfeld & Leighton, 2002;Tetlock, 1985), aggressive acts (Satterfield, 1998), competitive strategies (Kugler & Brodbeck, 2014;Walker & Watson, 1994), tension and stress (Suedfeld, 1992;, violence (Suedfeld, Tetlock, & Ramirez, 1977), and international crises (Ballard, 1983;Suedfeld & Bluck, 1988;. In contrast, higher levels of integrative complexity have been shown to be related to more cooperative agreements, peaceful resolutions (Koo, Han, & Kim, 2002;Liht, Suedfeld, & Krawczyk, 2005;Winter, 2007) and constructive inter-and intra-group processes (Brodbeck, Kugler, Fischer, Heinze, & Fischer, 2020;Park & DeShon, 2018). Hypothesis 1.…”
Section: Research Parameters For Assessing Complexity In Potentially mentioning
confidence: 94%
“…Different types of manipulations should be tested in future studies. For example, different levels of integrative complexity could be induced by presenting texts about topics unrelated to the focus of discussion, by conflict-facilitation techniques like the constructive controversy (Johnson et al, 2006), or through interactive discussion structures (Brodbeck et al, 2020). Furthermore, differences in the complexity of participants' emotions or behaviors could be manipulated in addition to their cognitions, which could have implications for the duration and sustainability of the induced effects.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire assessing participants' feelings and perceptions of the conflict scenario consisted of five scales: satisfaction with the relationship to the other party (four items), perceptions of mutuality between parties (three items), satisfaction with the interpersonal processes (four items), perceived attainment of one's own goals (three items), and satisfaction with the approach to the conflict (three items). The items were created by the authors for the purpose of this study but build on items used by Brodbeck et al (2011) as well as Kugler et al (2011).…”
Section: Methodsmentioning
confidence: 99%
“…However, the role of personality in group decision making has less been studied. These few studies include examining the role of the following personality dimensions in group-level decision making: dominance, personality types in computer-mediated group environments, personality in agent-based group decision making, personality traits of group decision leaders and followers, agreeableness in risky group decision making, integrative complexity personality traits, and personality traits in the social dilemma context (Brodbeck et al, 2021); Callaway et al, 1985;Santos et al, 2011;Thatcher & De La Cour, 2003;Wang et al, 2019;Zhang et al, 2021;Zheng, 2018). For this reason, the personality trait of group members is the first focus of this study.…”
Section: Role Of Conscientiousness Personality Trait In Group Decision Makingmentioning
confidence: 99%